2016
DOI: 10.1016/j.rmed.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged occupational exposure leads to allergic airway sensitization and chronic airway and systemic inflammation in professional firefighters

Abstract: These results indicate a "dose-response" effect of chronic exposure to a polluted environment on bronchial and systemic inflammation in professional firefighters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…Allergic airway sensitivity has been associated with inhalational exposure to combustion products, and occupational exposures have been associated with eosinophil production . A recent study among professional firefighters who had chronic and prolonged exposure to smoke and numerous ultrafine particulates reported statistically significantly higher percentage of eosinophils on induced sputum and bronchoalveolar lavage fluid testing compared with healthy subjects or firefighter trainees, and demonstrated a significant correlation between the percentage of sputum eosinophils and years of service . Identification of eosinophilic asthma versus non‐eosinophilic asthma has important implications for identification of potential causes and for selecting appropriate treatments .…”
Section: Discussionmentioning
confidence: 99%
“…Allergic airway sensitivity has been associated with inhalational exposure to combustion products, and occupational exposures have been associated with eosinophil production . A recent study among professional firefighters who had chronic and prolonged exposure to smoke and numerous ultrafine particulates reported statistically significantly higher percentage of eosinophils on induced sputum and bronchoalveolar lavage fluid testing compared with healthy subjects or firefighter trainees, and demonstrated a significant correlation between the percentage of sputum eosinophils and years of service . Identification of eosinophilic asthma versus non‐eosinophilic asthma has important implications for identification of potential causes and for selecting appropriate treatments .…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the high prevalence of OSA risk in the subjects of this study may be linked to potential pulmonary function problems in firefighters. 30 Excessive daytime sleepiness may be presented as a form of hypersomnolence which in turn, is one of the cardinal symptoms in depressive disorders. 31 Depression among firefighters is strongly associated with difficulties in emotion regulation that are commonly encountered in post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cardiovascular disease is the leading cause of excess morbidity and mortality in firefighters [9,42,43]. Some investigators have notice a higher incidence of respiratory and pulmonary symptoms as well as airways hyper-responsiveness and decay in lung function of firefighters during fire combat activities [9,81,82]. In addition, tobacco smoke is associated with the development of lung cancer among other types of cancers and diseases, namely leukemia and cancers of the urinary and aerodigestive tracts as well as of stomach, pancreas, liver, breast, prostate, and colorectal tissues [15].…”
Section: Cumulative Effects Of Tobacco Smoke and Fire Emissionsmentioning
confidence: 99%